THE ROLE OF LEGAL PHILOSOPHY IN THE FORMATING OF PROVINCIAL REGULATIONS: PERANAN FILSAFAT HUKUM DALAM PEMBENTUKAN PERATURAN DAERAH PROVINSI - Friskatati, Heti (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2024)
Indonesia is a democracy because its people are involved in policy-making. As a state of law, both rulers and citizens, as well as the nation itself are subject to the law. All attitudes, actions taken must be in accordance or based on the laws and regulations that apply in the Unitary State of the Republic of Indonesia. The emergence of laws and regulations is the result of the translation of public policy in the midst of the survival of a democratic society into a normative language order. Legal products are regulatory measures that need to be integrated into the regional autonomy system. High quality local legal products mean that these legal products include the preparation of material and technical regulations to solve problems and meet community needs. The formation of local legal products pays attention to the views, awareness, and legal ideals of life, including the spiritual atmosphere and the Indonesian state philosophy of Pancasila and the 1945 Constitution of the Republic of Indonesia. Regional legal products must be based on considerations and reasons that show that the direction of regional regulation is more democratic towards the formation of regional legal products that are really needed by the community. The normative legal research method is based on the idea of describing the research.